Motor performance of brazilian female artistic gymnasts: insights via multilevel analysis - Bacciotti, S.; Adam D. G.; Baxter, J.; Gaya, A.; Maia, J. (Science of Gymnastics Journal, 2019)
The aim of this research was to investigate individual and club-level variables that explain individual differences in gymnasts´ motor performance (MP). The sample was comprised of 249 female gymnasts (68 elite; 181 non-elite), aged between 9 and 20 years, split into four age categories: 9-10 years (n=98); 11-12 years (n=72); 13-15 years (n=64), and 16 and above (n=15). Gymnasts were from 26 Brazilian clubs, from six different states. The Talent Opportunity Program physical ability total test score was used to assess gymnasts` MP, based on a battery of seven tests: handstand hold, cast, rope climb, press handstand, leg flexibility, leg lift, and 20 meter sprint. Anthropometric, body composition, biological maturation, and training history data were also collected, as were club dimensions, infrastructures, competitions, manpower, and availability of selection/talent programs. Data were analyzed using a multilevel modelling approach. Individual gymnast` characteristics explained 39% of physical ability score variance from which 32% was related to the independent effects of age, competitive level, fat free mass, occurrence of menarche, and trainings hours per week (p < 0.05). Club characteristics explained 61% of gymnasts` total variance in physical ability score; 96% of this amount was related to club dimension, manpower, and talent program. These results reinforce the relevant role of the contextual effects and highlight the need to invest in club infrastructures: ideally in coaches` expertise and effective selection programs. Such investments should enable the enhancement and development of a gymnast`s careers during their lifetime involvement in training and competition. Keywords: physical fitness, performance, gym club.